(untitled) (Eureka Journal of Education & Learning Technologies, 2025)
The professional training of future teachers increasingly requires pedagogical models that support not only the acquisition of subject knowledge and instructional skills, but also the development of reflective thinking as a core professional competence. In contemporary educational systems, rapid social change, digital transformation, and growing diversity of learners place new demands on teachers’ ability to analyze their own practice, evaluate pedagogical decisions, and continuously improve professional performance. Within this context, reflective pedagogical approaches have gained particular importance as a means of fostering conscious, self-regulated, and ethically grounded teaching practice. This study examines the role and significance of reflective pedagogical approaches in the professional training of future teachers, focusing on their contribution to the formation of pedagogical awareness, professional identity, and adaptive competence. The research is grounded in theoretical perspectives from reflective practice theory, constructivist pedagogy, and teacher professional development studies. It conceptualizes reflection as a systematic cognitive and metacognitive process through which future teachers critically analyze learning experiences, teaching actions, and educational outcomes in order to enhance professional understanding and decision-making. The study highlights that reflective approaches shift teacher education from transmissive models toward learner-centered and inquiry-based paradigms, where students actively engage in self-assessment, peer feedback, and pedagogical analysis. Particular attention is given to the integration of reflective activities into coursework, teaching practicum, and pedagogical internships, including reflective journals, portfolios, case analysis, and guided mentoring. The findings indicate that consistent use of reflective pedagogical approaches contributes to deeper theoretical comprehension, improved instructional flexibility, and stronger alignment between pedagogical values and classroom practice. Moreover, reflection supports the development of critical thinking, professional responsibility, and readiness for lifelong learning, which are essential qualities for teachers operating in complex educational environments. The study also emphasizes the relevance of reflective pedagogy for pedagogical universities, where future teachers are expected to internalize professional standards and adapt to evolving educational policies and innovations. Overall, the research demonstrates that reflective pedagogical approaches play a decisive role in enhancing the quality of teacher preparation by transforming future teachers into active agents of their own professional growth, capable of critically engaging with educational challenges and contributing to sustainable educational development.